Future trade research areas that matter to developing country policymakers : a regional perspective on the Doha Development Agenda and beyond (United Nations, 2007)
This volume is a collection of papers and commentaries addressing current problems faced by trade policymakers, presented at the Post-Doha Research Agenda for Developing Countries Workshop in October 2006. The workshop was organized cooperatively by ESCAP and WTO as one of the first activities under the new project, the Macao regional Knowledge Hub in Support of Sustainable Trade and development (MARKHUB) sponsored by the government of Macao. Concern is expressed regarding some areas that might become problematic, such as preferential rules of origin, non-tariff barriers and behind-the border barriers.--Publisher's description
"United Nations pubication, sales no. E.08. II. F.3."
Keywords: World Trade Organization; World Trade Organization.; Free trade -- Government policy -- Developing countries -- Congresses; International trade -- Congresses; Commercial policy.; Free trade -- Government policy.; International trade.; Developing countries -- Commercial policy -- Congresses; Developing countries.; Conference papers and proceedings.